Social capital theory towards a methodological foundation - Häuberer, Julia (VS Verlag für Sozialwissenschaften, 2010)
The field of social capital still lacks a recognized general theory. Accordingly, various and sometimes inappropriate measurements are used for it. Julia Häuberer contributes to filling in this gap and provides progress towards the creation of a formalized social capital theory based on the founding concepts of social capital of Bourdieu (1983) and Coleman (1988), and current concepts of Putnam (2000), Burt (1992) and Lin (2001). The second part of the monograph focuses on the quality of measurements of the more general concept of social capital derived in the first part. Therefore, the telephone survey Social Relationships among Czech Citizens conducted as a test-retest experiment is analyzed. This book is valuable reading for academics in Sociology and Political Scien